2007
DOI: 10.1002/ccd.21110
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of bilateral arterial ducts in pulmonary atresia despite confluent branch pulmonary arteries: Opportunity for two percutaneous therapeautic alternatives

Abstract: We present a case of a newborn infant with double inlet left ventricle, pulmonary atresia, confluent pulmonary arteries, and bilateral arterial ducts (AD), to discuss the therapeutic alternatives offered by interventional catheterization techniques in this anatomic arrangement. The infant initially underwent stenting of the right AD to stabilize pulmonary blood flow off of prostaglandin infusion. Three weeks later, she developed left pulmonary artery isolation upon closure of the left arterial duct. An additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The authors suggested certain advantages of AD stenting over surgery: (1) Unbalance of lung perfusion and distortion of the pulmonary arteries can be prevented by having AD stents conform to the size and angulations of the pulmonary arteries; (2) Repeat stent dilation potentially adjusts the shunt size to the pulmonary artery growth. Texter et al reported stent placement on right AD followed by an additional stent in the pulmonary artery confluence for subsequent left pulmonary artery isolation, in a newborn with double inlet left ventricle, pulmonary atresia, confluent pulmonary arteries, and bilateral AD . In contrast, our patient had aortic valve atresia with IAA, resulting in pulmonary over‐circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested certain advantages of AD stenting over surgery: (1) Unbalance of lung perfusion and distortion of the pulmonary arteries can be prevented by having AD stents conform to the size and angulations of the pulmonary arteries; (2) Repeat stent dilation potentially adjusts the shunt size to the pulmonary artery growth. Texter et al reported stent placement on right AD followed by an additional stent in the pulmonary artery confluence for subsequent left pulmonary artery isolation, in a newborn with double inlet left ventricle, pulmonary atresia, confluent pulmonary arteries, and bilateral AD . In contrast, our patient had aortic valve atresia with IAA, resulting in pulmonary over‐circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Management of patients with bilateral AD is difficult and the condition is associated with significant mortality, due to the frequent coexistence of heterotaxy syndrome and complex congenital heart disease . Palliative stent placement has been performed in patients with bilateral AD, to stabilize pulmonary and systemic circulation and promote subsequent growth in these critical infants .…”
Section: Introductionmentioning
confidence: 99%